FEATURES OF THE C1431T POLYMORPHISM OF THE PPARG GENE IN ADULT PATIENTS WITH TYPE 2 DIABETES MELLITUS IN HOT CLIMATES - Abdullaeva Dilafruz Gayratovna; Khomidov Feruz Kasimovich; Abdullayeva Dilorom Telmanovna; Achilova Iroda Kadamovna (The Bioscan, 2024)
This article discusses the issueы of studying the genetic characteristics of adult patients сахарным with type 2 diabetes mellitus. The aim of the work is to introduce preventive measures for the prevention of type 2 diabetes. Material and methods. Clinical biochemical assays and PCR to determine polymorphism of the T/T, C/T and C/C alleles of the PPARG gene in the C1431T genotype. Results. The world is experiencing an increase in diabetes mellitus among different age groups, each country differs in its climatic, geographical and genetic characteristics. Taking them into account, it is necessary to develop a plan of preventive measures to solve the problem.